Validity and effectiveness of chemical practicum e-modules of various applications with ethnoscience approach in chemical learning: Analysis review - Jacky Anggara Nenohai; Sri Rahayu; I Wayan Dasna (Pascasarjana Universitas Negeri Medan, 2022)
This study intends to determine (1) the relevance of the practicum e module to the curriculum in chemistry learning; (2) the validity of the chemistry practicum e-module from various applications; and (3) the effectiveness of the application of the Ethnoscience-integrated chemistry practicum e-module in chemistry learning. This study uses the Systematic Literature Review (SLR) method using online article databases, namely ERIC and Google Scholar, which are limited to the last 5 years. The articles reviewed were 15 articles according to the topic. The results of the review show that the practicum e-module is in line with the curriculum in chemistry learning. Not to mention, practicum guides that go hand in hand with the times are very essential to be developed so that students can adapt well and learning becomes efficient with the current developing era. So, it is important to develop an electronic integrated practicum guide that creates balance between hard skills and soft skills in the curriculum concept. The validity of the chemistry practicum e-module from various applications in the implementation of online and offline practicum can be accepted by teachers and students, so that the teaching and learning process in proving theories in terms of practicum can be prepared. Especially in the future pandemic crisis, it is necessary to develop students' scientific literacy in terms of content, competence, context, and attitudes that are focused on preparing the next generation of scientific literacy through a culture-based curriculum to produce more contextual learning.Keywords: Ethnoscience approach, E-Module chemical practicum, Chemical learning